THE IMPORTANCE OF DEVELOPING ACADEMIC MOBILITY (ACTIVITY) IN STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses the importance of the development of academic mobility of university students. In this regard, studies were carried out by scientists-educators.